Study on the anti-hair loss effect of Black Ginseng - Yang Ting; Zhou Mingjuan; Liu Hanlin; Xu Mengdi; Qi Zhanwen; Qi Te; Liu Jinping; Wang Cuizhu; Geng Xiaoyu (Guoji laonian yixue zazhi)
[Objective] To establish an androgenic alopecia model in C57BL/6 mice, observe the improvement effect of Black Ginseng extract on alopecia, and explore its mechanism using network pharmacology and molecular docking methods. [Methods] An androgenic alopecia model was established by subcutaneous injection of testosterone propionate in mice. Different doses of Black Ginseng extract groups were set up and compared with Minoxidil. The improvement effect of Black Ginseng extract on androgenic alopecia was evaluated based on hair growth, dermal thickness, hair follicle morphology and count, serum hormone levels, and skin tissue VEGF and TGF-β content. Based on previous studies, the chemical constituents of Black Ginseng extract were identified. Swiss Target Prediction and Symmap databases were used to obtain targets of Black Ginseng’s chemical constituents, combined with alopecia-related targets from Malacard, DisGeNET, and Genecards databases to construct a "Black Ginseng-chemical composition-intersection target-alopecia" interaction network, screening key chemical components and targets, followed by molecular docking analysis. [Results] Mice in the Black Ginseng extract groups showed better hair growth than the model group, with increased dermal thickness, decreased serum testosterone and dihydrotestosterone levels, increased estradiol levels, increased VEGF expression, and decreased TGF-β expression in skin, all in a dose-dependent manner. Key chemical components Deoxyoleanolic acid, Ginsenoside Rb1, Ginsenoside Rg3, Ginsenoside Rh4, and Campesterol, as well as key targets INS, AR, VEGFA, PPARG, LEP, and CASP3, were identified. Molecular docking results showed stable binding between key components and targets. [Conclusion] Black Ginseng extract improves androgen-induced alopecia in mice, likely by regulating targets such as AR and pathways like MAPK. This provides a scientific basis for further research and development of Black Ginseng.